Economics working paper series - University of Wollongong. School of Economics and Information Systems (Wollongong, N.S.W. : School of Economics and Information Systems, University of Wollongong, 2003)
"The Economics working paper series is a publishing program of the School of Economics and Information Systems intended to provide a forum for debate and for the presentation of work-in-progress to a wider academic audience" --title screen.
Each issue has a distinctive title.
Title from title screen (viewed on October 23, 2003)
Mode of access: World Wide Web. Available at: http://www.uow.edu.au/commerce/econ/wplist.html
System requirements: Adobe Acrobat required to view/print PDF files.
Selected for archiving
Keywords: Economics -- Periodicals; Economics -- Australia -- Periodicals